Symmetric Dimethylarginine (SDMA) as Biomarker of Chronic Kidney Diseases in Dogs - Sonu,; Hariom,; Kumar, Ashok; Charaya, Gaurav (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Chronic renal failure is the loss of the ability of kidneys to excrete waste products, concentrate urine, electrolytes and fluid balance  leading to retention of creatinine, urea and other metabolic waste products in the body. The present study was planned to evaluate and  correlate Symmetric Dimethylarginine (SDMA) with the severity of chronic kidney disease (CKD) and with BUN and creatinine in dogs.  Twenty four dogs presented at Veterinary Clinical Complex of LLUVAS, Hisar (India), diagnosed to be suffering from renal failure on the  basis of history, clinical signs and ultrasonographic findings were included in the study. The dogs were divided into three categories  (atypical, mild and severe) based on the duration of presentation of cases after emergence of the clinical signs. Six apparently healthy  dogs were taken for comparsion with affected ones. Serum from all the affected and apparently healthy animals was used to evaluate  SDMA using ELISA kits, whereas BUN and creatinine were determined using biochemistry autoanalyzer. SDMA was significantly (20-fold)  elevated in dogs suffering from renal failure as compared to the control group. Significant (p
Keywords: Biomarker; BUN; Chronic renal failure; Creatinine; Dogs; SDMA